1975
DOI: 10.1021/bi00685a004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a new phosphatidylserine spin-label and calcium-induced lateral phase separation in phosphatidylserine-phosphatidylcholine membranes

Abstract: A new phosphatidylserine spin label with nitroxide stearate attached at the 2 position has been synthesized by the reaction of spin-labeled CDP-diglyceride with L-serine under the catalytic action of phosphatidylserine synthetase. Some structural properties of pure phosphatidylserine (PS) and binary PS-phosphatidylcholine (PC) membranes were studied with the spin label. PS membrane became solidified on lowering solution pH, 50% solidification being attained at pH 3.5. The membrane was also solidified by additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 21 publications
(13 reference statements)
5
39
0
2
Order By: Relevance
“…In this respect it is worth mentioning that in Staphylococcus aureus the indispensable to include the effect of electrostatic interactions on the phase behavior in biomembranes. To emphasize even further the key role played by the charges, we note that membranes composed of a binary mixture of charged lipids was reported to undergo a phase separation induced by addition of salt, even when the two lipids have same hydrocarbon tail [16][17][18] . For this charged lipid mixture, the segregation is mediated only by the electrostatic interaction between the lipids and the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect it is worth mentioning that in Staphylococcus aureus the indispensable to include the effect of electrostatic interactions on the phase behavior in biomembranes. To emphasize even further the key role played by the charges, we note that membranes composed of a binary mixture of charged lipids was reported to undergo a phase separation induced by addition of salt, even when the two lipids have same hydrocarbon tail [16][17][18] . For this charged lipid mixture, the segregation is mediated only by the electrostatic interaction between the lipids and the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Receivedfor publication 27 May 1977 and in revisedform 7 October 1977. 'Abbreviations used in this paper: BSA, bovine serum albumin; Buffer I, 0.15 M NaCl-O.01 M Tris, pH 7.4; DMD, is associated with proximal musele weakness and atrophy, cardiac involvement, and a high rate of varying degrees of mental retardation (1). Elevated levels of muscle enzyme activities in the serum and their depletioni in the mtuscle tissue have implied an abnormality in the plasma membrane as the probable site of the genetic defect, although the primary inherited metabolic defect is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that Ca 2+ can chelate with anionic lipids such as phosphatidylserines (PS) and induce the phase separation in the artificial cell membranes (phosphatidylcholine liposomes), though Mg 2+ less interacts with PS. [19][20][21][22] On the other hand, it was reported that the expression of PS in outer plasma membranes was more increased in the cancer cells as compared with in the normal cells. 23,24) Most recently, we have found the markedly inhibitory effects of extracellular Ca 2+ , but not Mg 2+ , on the growth of human stomach carcinoma (MKN-45) cells through the induction of apoptosis in vitro.…”
Section: Resultsmentioning
confidence: 99%